KONSEP AUDIT DAN PENGAWASAN DI BANK SYARIAH - Marina Marina (Cross-Border Journal of Business Management, 2023)
This article analyzes several important concepts, namely supervision of Islamic financial institutions, Islamic auditing framework, and corporate governance for Islamic financial institutions. The study was carried out by means of literature study referring to previous studies related to relevant topics. The results show that supervision of Islamic banks, Islamic auditing and corporate governance does not mean that they can replace the duties of bank management and do not guarantee that banks are free from crises, losses or bankruptcy. For this reason, Bank Indonesia should support Sharia banking supervision activities involving DSN and DPS. Sharia audits should also be carried out according to AAOFI audit standards. Meanwhile, corporate governance should be maximized in order to fulfill corporate social responsibility.